'[God] Is A Flaming Hebrew Letter': Esoteric Camp in Angels in America. (21st May 2019) - Kilner-Johnson, Allan
Abstract: This article turns attention to the mystical theology of Tony Kushner's Angels in America to demonstrate how Kushner aligns the long theological history of spiritual revelation and textual exegesis with the performative associations of camp, the stylised heightening of otherness, citation, and irony central to contemporary gay culture. Kushner's play underscores the role of the divinely-inspired interloper in the development of both Western religion and the esoteric currents which run beneath, defining mystical experience as a form of camp which has historically ascribed questionable alterity to the receiver. As this article maintains, this suggestive correlation between high camp and esoteric faith works to resist a positivism firmly rooted in the scientific materialism of modernity and which had previously served as the most consistent artistic and academic response to the HIV/AIDS crisis.